Smart district heating and electrification - Poul Alberg Østergaard; Henrik Lund (International Journal of Sustainable Energy Planning and Management, 2017)
District heating systems are prevailing in parts of Northern Europe and this editorial introduces work on the optimisation of such systems in Denmark, Britain and Norway. Focus of two of the articles are on low temperature systems. This is either directly through lowering the forward temperature and analysing system consequences and optimal forward temperatures as in the work of Lund et al. – or it is by the use of the return pipe water for heating in district heating system functioning at relatively high temperature levels, as in the work by Ianakiev on Nottingham. Analyses by Trømborg et al. probe into future Norwegian electricity market prices and their effects on the operation of district heating storage and electric boilers. Finally, Ogundari et al. compare photo voltaic systems to diesel systems in standalone systems for Abuja, Nigeria.